INOVASI PENGEMBANGAN DAN PENINGKATAN PELAYANAN PUBLIK PADA OBJEK WISATA TAMAN MARGASATWA MENGGUNAKAN METODE SOCIAL TRUST PATH - Oloan Sihombing; Muhammad Alfandi Hasibuan; Wenita Tarigan; Bijaksana Wa’ana (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Wildlife park is a means that can be used as a place to add understanding, knowledge, and insight that is fun for every tourists both for children, students and can be obtained by all tourists, because the function of the wildlife park in addition to being a tourist attraction is also a place of education. In an effort to develop and improve the service of wildlife park attractions visit is one of the factors in improving a service in the wildlife park so that tourists feel comfortable and safe to visit wildlife park attractions. Therefore, wildlife park attractions will further improve the service of visitation by creating a system as a medium of improvement of services in wildlife parks. In the use of a system will make an advantage in utilizing technology that is used as a medium of promotion of wildlife park attractions and also as a medium of information for tourists. Therefore, in the development and increase of wildlife park attractions, a high cooperation is required to increase visits in wildlife park.